Leadership in influencing and managing change in Ghanaian non-bank firms - Sanda, M. A.; Sraha, Y. (My University, 2011)
The purpose of this study was to determine the factors driving changes in the Ghanaian non-bank financial institutions and the roles of leaders in influencing organizational changes in Ghanaian non-bank financial institutions. The findings indicated that leaders are expected to create shared vision, put in place a plan, set strategy and deploy appropriate leadership styles that will inspire confidence in the workforce necessary to achieve set goals. It was found that leaders are not involving their workforce in the decision making process and their contributions were not valued as well. It is concluded that in order to achieve the full benefits of change, leaders create a shared vision and provide the strategies that will achieve results and at the same time galvanize the energies of the workforce towards a common goal